Metabolite profiling of Eragrostis nindensis during desiccation and recovery - Baluku, Erikan (Adolescent Health Research Institute, 2025)
Resurrection plants are a unique group of angiosperms that can withstand cellular water loss of up to 95% and resume full metabolic activity upon rehydration. To withstand extreme water loss, they employ a plethora of molecular, physiological, and biochemical processes including accumulation of metabolites that shield the plant cells from photo-oxidative damage and reactive oxygen species. A global understanding of the whole plant using a multi-omics approach will provide more insights into how different parts of the plant deal with desiccation. This study aimed to identify the different metabolites that are differentially abundant in Eragrostis nindensis at different stages of dehydration and rehydration time points in both desiccation-sensitive senescent (ST) and desiccation-tolerant non-senescent (NST) leaf tissue using gas chromatography-mass spectrometry Furthermore, this study compared the shoot and root systems to unravel similarities and differences at the whole plant level in overcoming desiccation. The metabolomics data from the shoots between NST and ST showed that differentially abundant metabolites in NST act as major drivers for plant desiccation tolerance and also aid the plant post-recovery. The roots accumulated fewer metabolites than the shoots; however, some specific metabolites were shown to accumulate exclusively in the roots. These findings revealed that E. nindensis exhibits a metabolic shift with the abundance of sugars such as raffinose and sucrose, amino acids such as glycine and glutamic acid and organic acids such as alpha-ketoglutaric acid and citric acid during dehydration, resulting in accumulation of desiccation-responsive metabolites predominantly in NST compared to ST. The results demonstrated that the leaves have a different metabolic shift pattern that is more variable, and the roots' metabolome is less affected by desiccation. Post- rehydration, there is an accumulation of amino acids and organic acids to aid in the resumption of metabolism in NST compared to ST and roots. The accumulation of these metabolites may protect E. nindensis from the damage associated with rapid drying, as the accumulation of similar metabolites identified in this study has been reported to function as osmoprotectants, reactive oxygen species quenchers and compatible solutes that replace water during desiccation. The identified metabolites and metabolic process provide a great insight into the goal of improving drought tolerance in orphan and drought-sensitive crops.